Antioxidant Activity and Total Phenolic Content of Benincasa Hispida Fruit Extracts From Various Extraction Solvents - Farah Hafidzah, Ahmad (2013)
The effects of solvent on the extraction of antioxidants and phenolic content from Benincasa hispida fruit were studied by conducting the DPPH scavenging analysis and total phenol content analysis (TPC). The main idea for this study is to determine the most effective solvents that show the highest antioxidant activities and TPC from fruit. The fruit were extracted with three different solvents: methanol, ethyl acetate and hexane by using 18 to 24 hours incubation in the dark flask at ambient temperature and pressure. The efficiencies of the solvents for the extraction of the antioxidants and phenolic were in ascending order: methanol > ethyl acetate > hexane. It was found that the phenolic content of the Benincasa hispida in the ranged between 3 mg/l to 12 mg/l in which equivalent to the tannic acid and methanol extract shows the highest TPC, followed by ethyl acetate and hexane. The overall study found that methanol was the most effective solvent for extracting of antioxidants and phenolic.